2021
DOI: 10.3171/2020.9.spine201010
|View full text |Cite
|
Sign up to set email alerts
|

Intradural calcium pyrophosphate dihydrate deposition disease: case report

Abstract: Calcium pyrophosphate dihydrate (CPPD) crystal deposition disease, also known as pseudogout, is a crystalline arthropathy that usually affects large joints and periarticular tissue. Spinal involvement is rare and is usually limited to extradural articular and periarticular structures. Only one case of intradural disease has been previously reported. The authors report the second known case of intradural CPPD deposition disease. An 81-year-old man presented with an 8-week history of urinary and fecal incontinen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“… 9 To that point, recent literature suggests that CPPD disease of the spine is not limited to the extramedullary space, bone, and surrounding tissues. Gewolb et al 10 and Chakravorty et al 11 demonstrated an intramedullary lesion positive for CPPD disease, an extremely rare presentation, which further adds to the atypical presentations of this disease.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 9 To that point, recent literature suggests that CPPD disease of the spine is not limited to the extramedullary space, bone, and surrounding tissues. Gewolb et al 10 and Chakravorty et al 11 demonstrated an intramedullary lesion positive for CPPD disease, an extremely rare presentation, which further adds to the atypical presentations of this disease.…”
Section: Discussionmentioning
confidence: 98%
“…Many descriptions of the lesions involve either radiographic evidence of calcification or gross pathology description of yellow turbid fluid or chalky white appearance, but these findings are not specific for CPPD disease. [1][2][3][4][5][6][7][8][9][10][11] As evidenced by the various presentations throughout the literature, there is no single pathognomonic finding except for visualization of positively birefringent rhomboid crystals on polarized microscopy. Therefore, polarized light analysis should become more commonplace in spinal pathology.…”
Section: Observationsmentioning
confidence: 99%
“…Intradural extramedullary CPPD presenting as an intradural soft tissue mass compressing the cauda equina nerve roots has been exceptionally reported. 37 38 Although CT may demonstrate the calcified nature of the mass and MRI a T1 and T2 hypointensity with minimal peripheral contrast enhancement, the diagnosis is usually made by the histologic analysis of the lesion. CPPD of the filum terminale was also reported.…”
Section: Crowned Dens Syndromementioning
confidence: 99%